Evaluate the Prevalence, Natural Course, and Final Visual Acuity in Patients with Stages III or IV of Diffuse Lamellar Keratitis Following Laser in Situ Keratomileusis - Afshin Mansourian; Bahman Sharifi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: And aim: The prevalence of DLK has been reported differently in different centers based onits severity. Hence, the aim of present study was evaluate the prevalence, natural course, and final visualacuity in patients with stages III or IV of diffuse lamellar keratitis following laser in situ keratomileusis.Methods: In the present descriptive study, 3941 eyes files from 2125 patients underwent LASIK surgery;were examined. All patients had a complete ophthalmologic examination before LASIK and had suitableconditions for LASIK.Result: Among the studied cases, 39 eyes (0.98%), out of 16 patients (0.75). The mean time intervalbetween LASIK and DLK diagnosis was 3± 2.4 days. A history of allergy was negative in all patients. Themean post-operative spherical refractive error in all eyes was in the range of 1 diopters and the averagecylindrical refractive error in 33 eyes was -0.66±1.2 diopters. The mean of final spherical refraction in34 eyes was 0.5±1.2 diopter and the mean of final cylindrical refraction in 35 eyes was -0.75±1.3 diopter.Severe turbidity at the flap surface in the first week decreased over time in all patients with stage III and IVDLK. So that only in four eyes (10.25%)Conclusion: The prevalence of stages III and IV in DLK is negligible compared to the large number ofLASIK procedures and all patients respond well to topical and systemic corticosteroid therapy.